-3(w+9)=-8w-2

Simple and best practice solution for -3(w+9)=-8w-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(w+9)=-8w-2 equation:



-3(w+9)=-8w-2
We move all terms to the left:
-3(w+9)-(-8w-2)=0
We multiply parentheses
-3w-(-8w-2)-27=0
We get rid of parentheses
-3w+8w+2-27=0
We add all the numbers together, and all the variables
5w-25=0
We move all terms containing w to the left, all other terms to the right
5w=25
w=25/5
w=5

See similar equations:

| y/3+20=31 | | (2x+4)•3=126 | | 10f-9=7+8+4f | | -6x=-7x-15 | | -58=-9x+5 | | 2x-5(x-4)=15 | | 7x+1=9-5x | | 11+17y+5=180 | | 7(x+3)+9=5(x-2)3x | | 4x+10=3(2x-12) | | 8+9p=3(3p-4) | | 3r=3/5 | | -9w+27=-4(w-8) | | -28-24k=-14 | | 6x-3=-3x-4 | | -8m=-7m+6 | | 10y+25=150 | | x-6=x−6=5x−2 | | -4(6x-4)=-36 | | 8n-16=4n+9 | | -55=-3k-7 | | 9(x-8)=-4x+6 | | 3y+4=44 | | 2(5x-3)-3x=5 | | -10-5r+8r=10+5r | | 3+10m=183 | | -100-12x=-17x+25 | | -4x-x-7=-7x+4 | | 6x-3=-3+1 | | -10-5r=8r+10+5r | | 2n+6-4n=2(n+9) | | 20-6(-3D+1)=-11d-19-4d |

Equations solver categories